"Året präglades av coronaviruspandemin" – Regeringar rapporterar om statligt ägda bolag i Finland och Sverige - Koskela, Merja; Enell-Nilsson, Mona (VAKKI ry, 2022)
The governments of Finland and Sweden report annually on state-owned companies. The reporting aims to motivate and legitimize state ownership and thus constitutes an example of sustainable public communication. In this article, we compare how the impact of the covid-19 pandemic shows in the sub-genre company overview, i. e. the parts of the reports where the profile and performance of individual companies are presented. The study is motivated by the fact that the pandemic has had significant economic and operational consequences although national strategies for coping with the pandemic have been different. The results show that the pandemic is represented in the company overviews of both countries mainly as a cause whose consequences are described in different ways. The negative consequences of the pandemic are emphasized, whereas positive consequences are downplayed, and neutral ones play a smaller role. Overall, the pandemic discourse in the company overviews is predominantly an economic discourse.
Keywords: covid-19-pandemin; diskurs; statsägda bolag; årsredovisning; fi=Markkinointi|en=Marketing|; fi=Viestintätieteet|en=Communication Studies|